2015
DOI: 10.1002/app.43082
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of p(AA‐co‐AM)/bent/urea and its swelling and slow release behavior in a simulative soil environment

Abstract: In this work, a novel slow release fertilizer contained 14.98% nitrogen was prepared via free radical polymerization of acrylic acid, acrylamide, and bentonite in the presence of cross‐linker (N,N′‐methylenebis acrylamide), initiator (potassium persulfate), and nutrient source (urea). The samples were analyzed using a Fourier transform infrared spectrometer, X‐ray diffraction, Scanning electron microscopy, Thermogravimetric analysis, and Brunauer, Emmett and Teller analysis. Results showed that the swelling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Bent is mainly composed of montmorillonite (MMT), whose structural unit consists of two tetrahedral layers (Si–O) separated by an octahedral layer (Al–O–OH) and is a good substrate for SAP with reactive −OH groups on the surface, high surface area, swelling capacity, and valuable cation exchange capacity. Furthermore, bent is environmentally friendly and readily available in large quantities at a low cost. Our previous studies indicated that incorporation of bent could improve water-retention capacity, swelling ability, thermal stabilities, and slow release properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Bent is mainly composed of montmorillonite (MMT), whose structural unit consists of two tetrahedral layers (Si–O) separated by an octahedral layer (Al–O–OH) and is a good substrate for SAP with reactive −OH groups on the surface, high surface area, swelling capacity, and valuable cation exchange capacity. Furthermore, bent is environmentally friendly and readily available in large quantities at a low cost. Our previous studies indicated that incorporation of bent could improve water-retention capacity, swelling ability, thermal stabilities, and slow release properties. , …”
Section: Introductionmentioning
confidence: 99%
“…has been used in our previous studies, and results have indicated that the incorporation of bent. can improve swelling ability, water-retention capacity (WR%), thermal stabilities, and slow-release properties. , However, the incorporation of SAPs into N-BC for water-retention enhancement has not yet been reported. In this work, SAPs have been introduced to combine with N-BC to obtain novel BSRFs with water-retention properties.…”
Section: Introductionmentioning
confidence: 99%
“…FTIR spectrum; (a) cellulose, (b) GEL-A before immersion, (c) GEL-B before immersion, (d) GEL-A after immersion, (e) GEL-B after immersionThe absorption peaks at wave numbers 3449 and 3445 cm -1 indicate the presence of the -OH group and the stretching of C-H was observed at wave numbers 2899 and 2928 cm -1[33]. Other peaks observed are absorption bands at wave numbers 1659 and 1603, 1377 and 1325-1419, and areas around 1000-1250 cm -1 , indicating the presence of carboxylic anion (-COO -) and N-H, as well as C-O or C-N[2,31,34]. Absorption peaks at wave numbers 611-671 and 602 cm -1 are associated with N-CO-N flexural vibrations, showing urea involvement in GEL-A and GEL-B[34].…”
mentioning
confidence: 98%
“…Other peaks observed are absorption bands at wave numbers 1659 and 1603, 1377 and 1325-1419, and areas around 1000-1250 cm -1 , indicating the presence of carboxylic anion (-COO -) and N-H, as well as C-O or C-N[2,31,34]. Absorption peaks at wave numbers 611-671 and 602 cm -1 are associated with N-CO-N flexural vibrations, showing urea involvement in GEL-A and GEL-B[34].…”
mentioning
confidence: 99%